Концептуалізація заздрості в зарубіжних психологічних дослідженнях - Мохорєва, О. М.; Mokhorieva, O. M. (Габітус. - 2023. - Вип. 51. - С. 222-228, 2023)
Досліджено різні теоретико-методологічні підходи дослідників до розгляду заздрості, її типів, складових, наслідків. Проаналізовано принципові розходження вчених щодо концептуалізації феномена заздрості як унітарної або дуальної конструкції; розглянуто коріння цієї диференціації, теоретичні та методологічні виклики, які вона передбачає. Показано, що найчастіше наукові студії зосереджувалися майже виключно на негативних наслідках заздрісності, увічнюючи сприйняття заздрості як аморальної та принизливої людської якості. Однак дослідження останніх десятиріч показали, що заздрісність може бути достатньо функціональною та призводити до різноманітних (іноді суперечливих) результатів, таких як соціально бажані реакції, соціально небажані реакції та до орієнтованих на емоції стратегій подолання. Окремі дослідники пропонують дуальний підхід до заздрісності, розрізняючи два типи заздрості: доброякісну (білу) заздрість, що включає висхідну мотивацію, і злісну (чорну) заздрість, що характеризується ворожістю до об’єкта заздрості.

The paper analyzes various theoretical and methodological approaches of researchers to the consideration of envy, its types, components, and consequences. The purpose of the work is to analyze the fundamental differences of scientists regarding the conceptualization of the phenomenon of envy as a unitary or dual construction; consider the roots of this differentiation, the theoretical and methodological challenges it implies. It is shown that most often scientific studies focused almost exclusively on the negative consequences of envy, perpetuating the perception of envy as an immoral and humiliating human quality. However, research in recent decades has shown that envy can be quite functional and lead to a variety of (sometimes contradictory) outcomes, such as socially desirable responses, socially undesirable responses, and emotion-focused coping strategies. Some researchers propose a dual approach to envy, distinguishing between two types of envy: benign (white) envy, which includes upward motivation, and malicious (black) envy, characterized by hostility to the object of envy. Works devoted to the so-called "white" (or "benign") envy have increased the attention of researchers to desirable reactions to envy. "Benign" envy, according to this concept, involves the motivation to improve oneself. However, a number of scholars insist that "white" and "black" envy in research are more appropriate to consider as benign and malicious subgroups of reactions to envy, rather than as separate types of envy. These authors emphasize that envy can lead to a sufficiently wide range of reactions, and therefore it is necessary to study it as a single integral characteristic. It is emphasized that the approach to envy as a holistic characteristic (without the division into "white" and "black") has greater prognostic utility. It is noted that the use of a unitary concept of envy allows researchers to meaningfully compare the results of empirical studies in order to obtain a comprehensive understanding of the phenomenon of envy.

Исследованы различные теоретико-методологические подходы исследователей к рассмотрению зависти, ее типов, составляющих, последствий. Проанализированы принципиальные различия ученых по концептуализации феномена зависти как унитарной или дуальной конструкции; рассмотрены корни этой дифференциации, теоретические и методологические вызовы, которые она предполагает.
Conceptualization of envy in foreign psychological research
Keywords: заздрість; envy; зависть; "чорна" заздрість; "black" envy; "черная" зависть; "біла" заздрість; "white" envy; "белая" зависть; доброякісна заздрість; benign envy; доброкачественная зависть; зловмисна заздрість; malicious envy; злонамеренная зависть; ворожість; hostility; враждебность; погляди вчених; views of scientists; взгляды ученых